Discourse: space for the constitution of the subject - Méndez Rivera, Pilar (Colombian Applied Linguistics Journal, 2012)
Discourse has been pointed as a site of struggle for power. However, when analyzing the teachers’ discourse of resistance to educational reforms has been privileged an orientation that prescribes discourse-power relations to mere relations of protest and opposition. This paper explores the relationship between subject, discourse and power in the Foucaultian perspective to make clear a relation discourse-power that enables the teacher to constitute himself as subject for practices of self-knowledge. As a context for the analysis of these relationships is used the speeches of teachers organized in the FECODE against educational reform around evaluation of learning and students promotion in Colombia, Decree 1290 of 2009, to identify ways of subject constitution, forms of resistance and delegitimation, revealing relationships between the state’s reform discourse and the collective subject teacher’s anti discourse. In this setting is important to note how discourses become spaces for the construction of subjectivities. Particularly, I am interested in analyzing the speeches of FECODE to analyze knowledgepower- resistance as a way teachers think of themselves collective subject of actions and knowledge to fight for their field of knowledge: evaluation of learning.